Matrix metalloproteinase-8 and substance P levels in root canal exudates of nonvital teeth - Su-Jung Shin; Woocheol Lee; Jae-Il Lee; Seung-Ho Baek; Kee-Yeon Kum; Won-Jun Shon; Kwang-Shik Bae (Korean Academy of Conservative Dentistry, 2011)
Objectives The aim of this study was to investigate levels of matrix metalloproteinase-8 (MMP-8) and substance P (SP) in root canal exudates during root canal treatment (RCT) of nonvital, painful teeth. Materials and Methods Patients scheduled for nonsurgical RCT were prospectively selected; the study was performed after obtaining informed consent from the patients and was approved by the Institutional Review Board for Clinical Research of Gangnam Severance Hospital, Yonsei University (3-2008-0118). Canal exudates samples were collected using sterilized paper points from teeth scheduled for RCT across three different time periods. MMP-8 and SP levels were measured using enzyme-linked immunosorbent assay (ELISA). Data were analyzed using a mixed model analysis and the Pearson correlation analysis (p < 0.05). Results MMP-8 and SP levels in GCF were decreased during RCT (p < 0.0001), and they showed a weak positive correlation to each other (p < 0.05). Patients'subjective pain levels and the response from percussion test were significantly related to SP level. Conclusions This study demonstrated that periradicular inflammation endodontic origin can elevate SP and MMP-8 levels in root canal exudates. Interestingly, SP level of canal exudates showed a possibility of being used as an indicator of pain due to periapical pathosis.